2021
DOI: 10.7592/ejhr2021.9.1.dulebova
|View full text |Cite
|
Sign up to set email alerts
|

The humorous dimension of intertextual relations in contemporary Slovak creolized media text

Abstract: In the article, we focused on the aspect of humour in the contemporary Slovak media discourse through the prism of the humorous potential of intertextuality. In order to grasp manifestations of intertextuality and understand how the intertextual joke functions, we turned to the concept of verbal and non-verbal precedent phenomenon (as the intertextual code of the linguo-cultural society) established in the modern Russian scholarship. Through the covers of the popular Slovak weekly .tyždeň from 2014-2019 (in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In particular, this involves the cases of creating a humorous effect in describing a situation that is, by its very nature, not comic. It is a frequent contrast between the seriousness of the subject and the look at it by the comic optics' [11]. The social satire that prevails in memes today articulates mostly serious social topics, but this does not prevent the emergence of a comic effect that is not linked to the humorous context of the thematized event, but is created as an effect of deceived expectation and the unpredictability of the transformation and subsequent re-semantization of the verbal or visual component of the meme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this involves the cases of creating a humorous effect in describing a situation that is, by its very nature, not comic. It is a frequent contrast between the seriousness of the subject and the look at it by the comic optics' [11]. The social satire that prevails in memes today articulates mostly serious social topics, but this does not prevent the emergence of a comic effect that is not linked to the humorous context of the thematized event, but is created as an effect of deceived expectation and the unpredictability of the transformation and subsequent re-semantization of the verbal or visual component of the meme.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of Internet memes, which Kanashina singles out in her publication, include virality, replicability, emotionality, seriality, mimicry, minimalism of form, polymodality, relevance, wit (comicality), publicness, and fantasy [10] Based on our observations, we would like to point out their intertextual nature as a key characteristic; for example, our analysis last year of a large corpus of polymodal texts from the covers of a popular Slovak magazine, .týždeň, demonstrated that they were mainly of intertextual nature, and referred both in their verbal and visual components to popular films, paintings, posters, and famous photos, as well as to precedent situations, names, texts and expressions of both historical and literary nature, while out of 271 analyzed covers (within the period of 5 years) 90 covers were of intertextual nature [11]. Similar conclusions are also made by Slovak media linguists who state that 'memes can be characterized by several basic properties: recurrence, intertextuality, contextuality, narrativity, and directness' [6] and that memes as units of cultural evolution are characterized by a high degree of variability and heritability [12].…”
Section: Precedent Phenomena As a Manifestation Of Intertextuality: Universal Precedent And National Precedent Phenomenamentioning
confidence: 99%
“…); научный дискурс (Первухина, 2022 и др. ); поликодовый текст в интернет-коммуникации (Мичурин, 2013;Щурина, 2014;Александрова, 2018;Рацибурская, Жданова, 2021;Dulebova, Krajchovichova, 2021;Моисеенко, Хервилья, 2021;Нестерова, 2022 и др.). Тем не менее необходимо отметить не вполне сложившуюся систему терминов, которыми пользуются лингвисты, занимающиеся теорией поликодового текста, что можно проследить на примерах пар терминов, смешиваемых или противопоставляемых в контексте анализа поликодового текста.…”
Section: Introductionunclassified